2018
DOI: 10.1136/openhrt-2017-000710
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction in stable cardiovascular disease using a high-sensitivity cardiac troponin T single biomarker strategy compared to the ESC-SCORE

Abstract: ObjectiveTo evaluate the prognostic performance of high-sensitivity cardiac troponin T (hs-cTnT) compared with the ESC-SCORE.MethodsWe included low-risk outpatients with stable cardiovascular (CV) disease categorised into need for non-secondary and secondary prevention. The prognostication of hs-cTnT at index visit was compared with the European Society of Cardiology-Systematic COronary Risk Evaluation (ESC-SCORE) with respect to all-cause mortality (ACM) and two composite endpoints (ACM, acute myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…When comparing hs-cTnT to a risk score developed by the European Society of Cardiology (ESC), elevated troponin levels were superior in predicting an adverse outcome. 155 More advanced testing could identify more patients at risk in this group but will require more resources and thus increase the strain on the health-care system.…”
Section: Cardiac Evaluation In Stable Chronic Diseasementioning
confidence: 99%
“…When comparing hs-cTnT to a risk score developed by the European Society of Cardiology (ESC), elevated troponin levels were superior in predicting an adverse outcome. 155 More advanced testing could identify more patients at risk in this group but will require more resources and thus increase the strain on the health-care system.…”
Section: Cardiac Evaluation In Stable Chronic Diseasementioning
confidence: 99%
“…Outside the scope of ACS, several studies have also found an association between elevated cTn levels and risk of death. In patients with stable coronary heart disease, a greater risk for cardiovascular mortality and incidence of heart failure has been found in those with higher levels of hs-cTnT 26 - 28 and hs-cTnI. 29 Elevated circulating hs-cTnT was also shown to be independently associated with higher mortality in outpatients with stable heart failure, 30 , 31 and in patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…Also, so-called uremic cardiomyopathy may contribute to the level of troponin by different mechanisms, including uremia-induced structural changes in the myocardium, endothelial dysfunction, loss of membrane integrity, and ’leaking’ of troponin from cardiomyocytes. Certain studies suggest that troponin is a more prognostic than diagnostic biomarker [ 48 ]. In the present study, the patients with registered CV events had higher values of troponin, but its predictive power was not confirmed by Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%